Analisis Faktor Risiko Kejadian Diabetes Mellitus Tipe II di Wilayah Pedesaan - Wijayanti, Siwi Pramatama Mars; Nurbaiti, Tias Tri; Maqfiroch, Arrum Firda Ayu (Jurnal Promosi Kesehatan Indonesia, 2020)
Background: Diabetes mellitus (DM) is a non-communicable disease that remains a significant health concern in Indonesia. The disease is more prevalent in urban areas due to lifestyles, socioeconomics level and lack of physical activity. Currently, DM has begun occured also in rural areas. The purpose of this study is to identify the risk factors associated with Type II DM incidence in rural areas.Method: This is analytical study with a case-control design, located in Community Health Centre 1, Wangon, Banyumas Regency. There are 65 people in case group and 65 people in control group involved in this study. Variables included personal characteristics, dietary habit, physical activity and exposure to cigarette smoke. Data was obtained by structured questionnaire and analyze using univariate, bivariate (chi-square test) and multivariate analysis (logistic regression test).Results: The results showed that the dietary habit (OR = 11,824; 95% CI = 4,988-28,032) and physical activity (OR = 2,608; 95% CI = 1,116–6,095) had influenced on the incidence of DM type II. Whilst the exposure of cigarette smoking did not influenced the incidence of DM type II. It is suggested that consume foods with balanced nutrition and doing physical activities should be conducted routinely in accordance with WHO recommendations.